Thrombin and Factor Xa Hydrolysis of Chromogenic Substrates in the Presence of Sulfated Derivatives of Galactomannan and Galactoglucomannan Natural Gels - Natalia N. Drozd; Svetlana A. Kuznetsova; Yuriy N. Malyar; Aleksandr S. Kazachenko; Valentina S. Borovkova; Yarosvala D. Berezhnaya (Pharmaceutics, 2022)
Polysaccharides are important structural components of all plant species. Gel-like polysaccharides have found wide application in various fields, including medicine, construction, and the food industry. In the present work, galactomannan and galactoglucomannan gel-like polysaccharides were modified with sulfate groups and their anticoagulant activity was studied. Sulfation with chlorosulfonic acid in pyridine and with sulfamic acid in pyridine and a sulfamic acid–urea deep eutectic solvent were used as synthesis routes. The resulting gel-like polysaccharide sulfates were studied by elemental analysis, Fourier-transform infrared spectroscopy, and gel permeation chromatography. It was established that the anticoagulant effect of sulfated galactoglucomannan (SGGM) and galactomannan (SGM-1 and SGM-2) is related to an independent antithrombin-independent decrease in the amidolytic activity of thrombin and factor Xa. It is shown that the inhibitory activity of SGGM and SGM-2 against the collagen-induced platelet aggregation can be an additional factor in selecting compounds that are most promising for modifying polymer surfaces to ensure resistance to blood clotting.